THE MODEL OF THE EFFECT OF LEADERSHIP AND WORK DISCIPLINE ON WORK ACHIEVEMENT: A CASE STUDY OF PERSONNEL IN INDONESIA - Esti Liana (ABNUS Publisher, 2021)
The objectives of this study are: 1) To determine the influence of leadership on the performance of personnel in Indonesia. 2) To determine the effect of work discipline on the work performance of personnel in Indonesia. 3) To determine the effect of leadership and work discipline together on the work performance of personnel in Indonesia.” This “research approach is quantitative, descriptive and associative. The population in this study were 110 personnel in government agencies in Indonesia. In this study the authors narrow the population by calculating the sample size using the Slovin technique. So the number of samples studied were 52 respondents”. The results of this study indicate that: 1) There is an influence of leadership on the work performance of personnel. 2) There is an influence of work discipline on the work performance of personnel. 3) There is an influence of leadership and work discipline together on the work performance of personnel.